2017
DOI: 10.1111/tmi.12850
|View full text |Cite
|
Sign up to set email alerts
|

Pyrethroids and DDT tolerance of Anopheles gambiae s.l. from Sengerema District, an area of intensive pesticide usage in north‐western Tanzania

Abstract: Abstractobjective To assess the susceptibility status of malaria vectors to pyrethroids and dichlorodiphenyltrichloroethane (DDT), characterise the mechanisms underlying resistance and evaluate the role of agro-chemical use in resistance selection among malaria vectors in Sengerema agro-ecosystem zone, Tanzania.methods Mosquito larvae were collected from farms and reared to obtain adults. The susceptibility status of An. gambiae s.l. was assessed using WHO bioassay tests to permethrin, deltamethrin, lambdacyha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 45 publications
1
23
0
Order By: Relevance
“…The wide coverage of LLINs is thought to have contributed to the development of insecticide resistance in the local malaria vectors population due to the insecticide selection pressure encountered by vectors [ 9 , 17 ]. Many vector species have developed resistance to one or more classes of insecticides commonly used in Tanzania [ 18 20 ]. Development of vector resistance may be caused by many factors including overuse of insecticides by ITNs, IRS, and household pest control or by agricultural pesticides use [ 19 , 21 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…The wide coverage of LLINs is thought to have contributed to the development of insecticide resistance in the local malaria vectors population due to the insecticide selection pressure encountered by vectors [ 9 , 17 ]. Many vector species have developed resistance to one or more classes of insecticides commonly used in Tanzania [ 18 20 ]. Development of vector resistance may be caused by many factors including overuse of insecticides by ITNs, IRS, and household pest control or by agricultural pesticides use [ 19 , 21 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…The majority of these studies have demonstrated the toxicological effects of these compounds in animals and humans (Singh, ; Turusov et al, ; Wang et al, ). Although simultaneous exposure to DDT and PMT was demonstrated (Bouwman & Kylin, ; Gunier et al, ; Philbert et al, ; ul Hassan et al, ; Xu et al, ), the toxic effects caused by the DDT + PMT interaction remain unknown and are rarely studied. In this study, we have used metabolomics‐on‐a‐chip approach to investigate the effect of DDT, PMT and DDT + PMT mixture on liver cells.…”
Section: Discussionmentioning
confidence: 99%
“…Although DDT has been prohibited in most countries since 1970, it remains widespread in the environment at high concentrations because of its high resistance to degradation (Hurd‐Brown et al, ; Shi et al, ). Moreover, DDT is still used in countries in which malaria is a public health problem (Chaumeau et al, ; Philbert, Lyantagaye, Pradel, Ngwa, & Nkwengulila, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many modern analytical methods for pyrethroids detection have been reported, such as GC with electron capture detection and GC–MS . However, the concentrations of analytes are very low and the sensitivity of direct detection is often inadequate in complex matrix.…”
Section: Introductionmentioning
confidence: 99%